Promoting Organizational Citizenship Behavior in Public Sector Human Resource Management: A Study of the Asmat Regency Government - Amiyaram, Absalom (KnE Social Sciences, 2025)
Organizational citizenship behavior (OCB) plays a significant role in enhancing the performance and responsiveness of public institutions. In the context of regional government, especially in remote areas like Asmat Regency, the cultivation of OCB among civil servants is crucial for delivering effective public services. This study explores the promotion of OCB within the framework of human resource management (HRM) in the public sector, focusing on how the Government of Asmat Regency develops, encourages, and sustains OCB among its personnel. Using a qualitative approach, this research analyzes managerial strategies, institutional culture, leadership influence, and employee motivation as key factors influencing OCB. The findings are expected to contribute to the formulation of HR policies that align with local needs while fostering voluntary, collaborative, and civic-minded behaviors in government employees.